2020
DOI: 10.1002/1348-9585.12118
|View full text |Cite
|
Sign up to set email alerts
|

Work-related injuries and illnesses and their association with hour of work: Analysis of the Oregon construction industry in the US using workers’ compensation accepted disabling claims, 2007-2013

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…The NR-36 adverted that a rest break should not occur in the first hour of work (Brasil, 2013). Conforming to disabling claims data of 12,222 workers of the construction industry from 2007 to 2013, it was identified that the 5th and 13th hours corresponded to significantly more severe injuries and illnesses than in the first hour of work (Yang et al, 2020). Some workers, in the current study, cited that they preferred a higher frequency of breaks so as not to work for long periods (after the main meal).…”
Section: Discussionmentioning
confidence: 55%
“…The NR-36 adverted that a rest break should not occur in the first hour of work (Brasil, 2013). Conforming to disabling claims data of 12,222 workers of the construction industry from 2007 to 2013, it was identified that the 5th and 13th hours corresponded to significantly more severe injuries and illnesses than in the first hour of work (Yang et al, 2020). Some workers, in the current study, cited that they preferred a higher frequency of breaks so as not to work for long periods (after the main meal).…”
Section: Discussionmentioning
confidence: 55%
“…In a study of occupational injury among US construction workers with compensation‐accepted disabling claims from 2007 to 2013, the number of workers showed a consistent decrease from 2840 claims in 2007 to 1260 in 2013, and the rate per 100 workers also had decreased from 2.73 in 2007 to 1.70 in 2013. 31 The mortality rate significantly increased by 1.04 times every year, from 16.75 in 2012 to 21.91 in 2018. In a study analyzing occupational injury trends in major countries, including Korea, the mortality rate due to occupational injuries in Korea was 0.361 in 2018, higher than that in the United States (0.337), the United Kingdom (0.045), and Japan (0.126).…”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to the trend of decreasing the occupational injury rate in other countries such as the United States. In a study of occupational injury among US construction workers with compensation‐accepted disabling claims from 2007 to 2013, the number of workers showed a consistent decrease from 2840 claims in 2007 to 1260 in 2013, and the rate per 100 workers also had decreased from 2.73 in 2007 to 1.70 in 2013 31 . The mortality rate significantly increased by 1.04 times every year, from 16.75 in 2012 to 21.91 in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Certain occupations exist that work in potentially dangerous environments, such as, but not limited to, construction workers [ 1 ], underground coal miners [ 2 ], and tactical professionals, inclusive of military personnel [ 3 ], firefighters [ 4 ], and law enforcement [ 5 ]. Due to these potentially hazardous environments, persons working in these occupations wear specialised personal protective equipment (PPE).…”
Section: Introductionmentioning
confidence: 99%